Nonlinear control of GTI for stabilizing future smart grids - Salam Ibrahim Khather (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The most important components of the distributed generation frameworks is the GTIs which is an interface amidst the utility and the source of energy. The recent years have seen an increased interest in the design and usage of GTIs due to its smaller weight and size, low cost and higher efficiency. But the problem of leakage currents in the transformerless inverter that is dependant on its topology and control scheme needs to be looked into carefully. Also, the high performance of the GTI requires a stringent control and various control systems are being developed and applied to the GTIs. This paper reviews the various topologies that are classified based on the attributes of the leakage current and the method of decoupling. Further it reviews and compares the different control techniques applied to the GTIs with respect to the frame of reference, controller, modulation technique and the control parameters considered.